External Counterpulsation Improves Angiogenesis by Preserving Vascular Endothelial Growth Factor-A and Vascular Endothelial Growth Factor Receptor-2 but Not Regulating MicroRNA-92a Expression in Patients With Refractory Angina - Ambari, Ade Meidian; Lilihata, Gracia; Zuhri, Ervan; Ekawati, Elok; Wijaya, Shoma Adhi; Dwiputra, Bambang; Sukmawan, Renan; Radi, Basuni; Haryana, Sofia Mubarika; Adiarto, Suko; Hanafy, Dicky A.; Zamroni, Dian; et al. (Frontiers in Cardiovascular Medicine, 2021)
OBJECTIVE: External counterpulsation (ECP) provides long-term benefits of improved anginal frequency and exercise tolerance in refractory angina (RA) patients. This is postulated as a result of improved angiogenesis and endothelial function through increased in shear stress. Angiogenesis is mainly regulated by Vascular Endothelial Growth Factor-A (VEGF-A) and its receptor Vascular Endovascular Growth Factor Receptor-2 (VEGFR-2). miR-92a is a flow-sensitive miRNA that regulate atherosclerosis and angiogenesis in response to shear stress. Thus, ECP beneficial effect might be achieved through interaction between VEGF-A, VEGFR-2, and miR-92a. This study aims to evaluate the ECP effect on VEGF-A, VEGFR-2, and miR-92a in RA patients in a sham-controlled manner. METHODS: This was a randomized sham-controlled trial, enrolling fifty RA patients with coronary artery disease. Participants were randomized (1:1 ratio) to thirty-five sessions of either ECP (n = 25) or sham (n = 25), each session lasting for one hour. Plasma levels of VEGF-A and VEGFR-2 were assayed by ELISA technique. The quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was performed to measure miR-92a circulating levels in plasma. RESULT: ECP significantly preserved VEGF-A and VEGFR-2 level compared to sham [ΔVEGF-A: 1 (-139 to160) vs -136 (-237 to 67) pg/ml, p = 0.026; ΔVEGFR-2: -171(-844 to +1166) vs -517(-1549 to +1407) pg/ml, p = 0.021, respectively]. Circulating miR-92a increased significantly in ECP [5.1 (4.2 – 6.4) to 5.9 (4.8 – 6.4), p<0.001] and sham [5.2 (4.1 – 9.4) to 5.6 (4.8 – 6.3), p=0.008] post intervention. The fold changes tended to be higher in ECP group, although was not statistically different from sham [fold changes ECP = 4.6 (0.3 - 36.5) vs sham 2.8 (0 -15), p = 0.33)]. CONCLUSION: ECP improved angiogenesis by preserving VEGF-A and VEGFR-2 levels. Both ECP and sham increased miR-92a significantly, yet the changes were not different between the two groups. (Study registered on www.clinicaltrials.gov, no : NCT03991871, Aug 8, 2019, and received grant from National Health Research and Development of Ministry of Health of Indonesia, No : HK.02.02/I/27/2020).